Low-temperature thermal conductivity of thermoelectric Co1−xMxSi (M = Fe, Ni) alloys. (June 2021) - Ivanov, Y.; Levin, A.A.; Novikov, S.; Pshenay-Severin, D.; Volkov, M.; Zyuzin, A.; Burkov, A.; Nakama, T.; Schnatmann, L.; Reith, H.; Nielsch, K.
Abstract: We study the low-temperature electrical and thermal conductivity of CoSi and Co1− x M x Si alloys (M = Fe, Ni; x  ≤ 0.06). Measurements show that the low-temperature electrical conductivity of Co1− x Fe x Si alloys decreases at x  > 0.01 by an order of magnitude compared with that of pure CoSi. It was expected that both the lattice and electronic contributions to thermal conductivity would decrease in the alloys. However, our experimental results revealed that at temperatures below 20 K, the thermal conductivity of Fe- and Ni-containing alloys is several times larger than that of pure CoSi. We discuss possible mechanisms of the thermal conductivity enhancement. The most probable one is the dominant scattering of phonons by charge carriers. We propose a simple theoretical model that takes into account the complex semimetallic electronic structure of CoSi with nonequivalent charge carrier pockets. This model explains well the increase of the lattice thermal conductivity with increasing disorder and the linear temperature dependence of thermal conductivity in the Co1− x Fe x Si alloys below 20 K. Graphical abstract: Image 1 Highlights: Electrical resistivity of Co1-x Fex Si alloys is very large compared with pure CoSi. Low-temperature thermal conductivity of Co1-x Fex Si is several times higher than that of CoSi. Ineffectiveness of phonon–electron interaction in disordered alloys is discussed. Phonon relaxation because of interband electron transitions in complex band structure of CoSi is calculated.